1998
DOI: 10.1097/00005392-199809020-00019
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Vesicoureteral Reflux Practice Pattern Survey Among American Academy of Pediatrics, Section on Pediatric Urology Members

Abstract: Today there is substantial consensus among urologists on many issues regarding vesicoureteral reflux management. However, the areas of controversy will only be clarified by further scientific and clinical outcomes based research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Ferrer et al evaluated 155 surveys from pediatric urologists and found general agreement in the diagnostic workup of VUR patients and those with febrile UTIs, however, the indications for treatment were not as clear. 10 While common reasons to choose surgical intervention include severity and frequency of UTI, renal scarring, and persistence of reflux, no standard algorithm has been accepted. Furthermore, the choice of endoscopic or open surgical intervention lacks a specific algorithm and leaves the recommended procedure to each surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrer et al evaluated 155 surveys from pediatric urologists and found general agreement in the diagnostic workup of VUR patients and those with febrile UTIs, however, the indications for treatment were not as clear. 10 While common reasons to choose surgical intervention include severity and frequency of UTI, renal scarring, and persistence of reflux, no standard algorithm has been accepted. Furthermore, the choice of endoscopic or open surgical intervention lacks a specific algorithm and leaves the recommended procedure to each surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, open antireflux surgery or subureteric injection of biocompatible agents leading to mass effect (endoscopic therapy) have been widely used in recurrent urinary tract infections in spite of antibiotic prophylaxis in patients with VUR, in cases of development of new scars on scintigraphy or ongoing reflux during a few years of follow-up [11]. PPC is a new nonabsorbable and biocompatible injection material used in the endoscopic treatment of VUR [14].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the particles have an average diameter of 300 μm. Therefore, the risk of migration is low [11]. …”
Section: Introductionmentioning
confidence: 99%
“…35 In the United States, adoption of these approaches has been mixed, with wide variations noted in imaging practices nationally. 2,14,15 …”
Section: Discussionmentioning
confidence: 99%